INTEGRATED IDENTITY AS A PSYCHOLOGICAL DETERMINANT OF A PERSON’S HARMONIOUS EATING BEHAVIOR - Bonkalo; Shmeleva; Zavarzina; Strelkov; Aralova; Kachalov (Revista Inclusiones, 2020)
The article is devoted to one of the topical and globally important problems – the problem of eating disorders of young people. The authors focus on the identification of psychological factors that determine the styles of eating behavior. The article reveals the degree of its development in modern psychology and psychiatry, determines the methodological approach and organization of the study. The study is based on the psychodynamic approach and the Central provisions of the concept of dynamic psychiatry according to which, the structure of the individual is considered in relation to the totality of its relations. It is a certain combination of varying degrees of Central and unconscious Self-functions that make up its identity. Violations of identity as a General disharmonization of the personality structure determine the occurrence and development of personality and behavioral disorders due to the disintegration of its basic Self-functions.